Comparison of Three Devices to Measure Pressure for Acute Compartment Syndrome. (13th February 2020) - Merle, Geraldine; Comeau-Gauthier, Marianne; Tayari, Vahid; Kezzo, Mohamad Nizar; Kasem, Chrouk; Al-Kabraiti, Faisal; Laverdiere, Carl; Xereas, George; Harvey, Edward J
Abstract: Introduction: Acute compartment syndrome (ACS) is a well-recognized and common emergency. Undiagnosed ACS leads to muscle necrosis, limb contracture, intractable pain, and may even result in amputation. Methods: Three devices (Synthes, Stryker, and MY01) were compared in a pre-clinical rat abdominal compartment syndrome simulation. Simultaneous measurements of intracompartmental pressures allowed concurrent comparison among all devices. Results: Large variations from the reference values are seen with the Synthes and Stryker devices. Variances are large in these two devices even under ideal conditions. The MY01 device was the truest indicator of reference pressure in this ACS model (over 600% more accurate). Conclusions: The MY01 device was the most accurate device in tracking pressure changes in this rat model of abdominal compartment syndrome.